Il nuovo protagonismo delle donne migranti: la partecipazione ai movimenti per il diritto all’abitare - Colella, Francesca (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
In recent decades, social movements have expanded their range of action, adopting a more global perspective. Although many studies have been made on several national and transnational movements, it still remains very little studied the participation that involves of immigrants, especially women, in social movements in Italy. These movements involve several issues: the right to work, the political participation, freedom of religion and the housing crisis. The thematic focus of our research is the housing issue, at the national level, and our case study concerns the situation of the women immigrants participation in movements for the housing rights in Rome. At a time when it seems to be less public interest in economic, social and cultural rights (such as the rights to education, work, house and health) in favor of a broader interest in individual rights (freedom of opinion, freedom of geographical movement, freedom of expression etc.), studying the role of immigrant women in the participation in social movements for the right to house in the destination countries can encourage and support a renewed attention to this area. The changing social composition of the resident population and the emergence of old and new forms of poverty - the incoming immigration flows are one of its main causes – affect significantly this issue. As we can see, the figure of the immigrant transforms the housing problem into a problem of co-habitation, or even better, of co-existence.